In-plane free vibration and response analysis of isotropic rectangular plates using the dynamic stiffness method. (May 2015) - Nefovska-Danilovic, M.; Petronijevic, M.
Highlights: We developed dynamic stiffness matrix of rectangular plate for in-plane vibration. We calculated natural frequencies of plates with different boundary conditions. We calculated dynamic response of plate subjected to harmonic line load. Presented results showed a very good agreement with the results from the literature. Presented method showed high precision and accuracy in comparison with FEM. Abstract: The development of the dynamic stiffness matrix for isotropic rectangular plate with arbitrary boundary conditions undergoing in-plane free vibration is presented in this paper. Gorman's superposition method is exploited to obtain the solution of the governing equations of motion. The dynamic stiffness matrix is derived using the Projection method. The obtained results are in good agreement with the results obtained using exact solutions for some special cases and also with finite element solutions. Modeling of plates undergoing in-plane vibration using dynamic stiffness method demonstrate high precision, accuracy and low memory requirement in comparison with the finite element method.